Pemanfaatan Tanaman Kacang Panjang untuk Mengendalikan Hama Ulat pada Tembakau di Desa Jambearum Kecamatan Puger Kabupaten Jember - Alwi Alkaff; Nur Hidayah; Siti Nur Azizah; Agustia Zulfia N.B; Imro’atus Solehah (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2023)
Tobacco is the largest foreign exchange for the country. So for some countries, including Indonesia, it plays a role in the national economy. The central statistics agency. noted that East Java was the province with the largest tobacco plantation area in Indonesia. One of them is the tobacco and pasat tobacco (H8). The purpose of this study was to analyze caterpillar pest on conducting interviews surveys to farmers using purposive sampling method. Where the researcher determines the sampling by establishing special characteristic that are in accordance with the research objectives. The results of the study obtained information that the caterpillar pest is often a constraint on tobacco plants. Meanwhile, there is a shortage of fertilizes and causes prices to skyrocket. If it continuous, this can result in huge losses because the output issued is greater than the input received.